2015
DOI: 10.1016/j.media.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricle segmentation from cardiac MRI: A collation study

Abstract: Magnetic Resonance Imaging (MRI), a reference examination for cardiac morphology and function in humans, allows to image the cardiac right ventricle (RV) with high spatial resolution. The segmentation of the RV is a difficult task due to the variable shape of the RV and its ill-defined borders in these images. The aim of this paper is to evaluate several RV segmentation algorithms on common data. More precisely, we report here the results of the Right Ventricle Segmentation Challenge (RVSC), concretized during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
145
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(149 citation statements)
references
References 51 publications
4
145
0
Order By: Relevance
“…However, most of researches focus on the left ventricle (LV) segmentation because the LV is the biggest chamber of heart [3][4][5]. Compared to the LV, the segmentation problems of RV get more and more attentions in recent years, along with the increasing cognition about the function of RV [6][7][8]. For instance, some cardiac diseases such as pulmonary hypertension, cardiomyopathy and dysplasia, are all related to the RV.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of researches focus on the left ventricle (LV) segmentation because the LV is the biggest chamber of heart [3][4][5]. Compared to the LV, the segmentation problems of RV get more and more attentions in recent years, along with the increasing cognition about the function of RV [6][7][8]. For instance, some cardiac diseases such as pulmonary hypertension, cardiomyopathy and dysplasia, are all related to the RV.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed method was evaluated over a data set composed of 48 subjects provided by the RVSC, MICCAI 2012 [16] and a data set composed of 23 Hypoplastic Left Heart Syndrome (HLHS) patients. For the moving mesh, grid sampling was set equal to the pixel spacing.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed method was evaluated over the training and testing sets provided by the RVSC [16]. Each data set consists of short-axis MRI volumes of 16 subjects.…”
Section: Rv Segmentation Challenge Datamentioning
confidence: 99%
See 1 more Smart Citation
“…There is a wide range of multi-atlas based approaches addressing the problem of cardiac segmentation [7]. We have selected to use the segmentation pipeline proposed by Zuluaga et al [10] as it has shown to be robust in the segmentation of different structures within the heart [13,14]. The details of the presented method can be found in [10].…”
Section: Methodsmentioning
confidence: 99%